2016
DOI: 10.1038/srep22360
|View full text |Cite
|
Sign up to set email alerts
|

ES1 is a mitochondrial enlarging factor contributing to form mega-mitochondria in zebrafish cones

Abstract: Total mass of mitochondria increases during cell proliferation and differentiation through mitochondrial biogenesis, which includes mitochondrial proliferation and growth. During the mitochondrial growth, individual mitochondria have been considered to be enlarged independently of mitochondrial fusion. However, molecular basis for this enlarging process has been poorly understood. Cone photoreceptor cells in the retina possess large mitochondria, so-called mega-mitochondria that have been considered to arise v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 39 publications
5
35
1
Order By: Relevance
“…In addition, LOC422305 and MCOLN2, found to be significantly downregulated in cells infected with D78 relative to those infected with UK661, were also included in this group, making a total of 18 genes. The LOC422305 gene encodes the mitochondrial-like ES1 protein [21], and the MCOLN2 gene encodes the ion channel TRPML2 [22] that has been reported to enhance the replication of yellow fever and dengue viruses [23,24]. The other three groups comprised the 53 genes that were transcribed to a higher level in D78-infected cells relative to mock-infected cells, as well as the two genes that were significantly up-regulated by infection with D78 relative to infection with UK661 (HBG2 and HSP25), making a total of 55 genes.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, LOC422305 and MCOLN2, found to be significantly downregulated in cells infected with D78 relative to those infected with UK661, were also included in this group, making a total of 18 genes. The LOC422305 gene encodes the mitochondrial-like ES1 protein [21], and the MCOLN2 gene encodes the ion channel TRPML2 [22] that has been reported to enhance the replication of yellow fever and dengue viruses [23,24]. The other three groups comprised the 53 genes that were transcribed to a higher level in D78-infected cells relative to mock-infected cells, as well as the two genes that were significantly up-regulated by infection with D78 relative to infection with UK661 (HBG2 and HSP25), making a total of 55 genes.…”
Section: Resultsmentioning
confidence: 99%
“…There are hundreds of mitochondria in zebrafish cones packed tightly between the nucleus and outer segment. Previous studies revealed that these mitochondria are heterogeneous (Kim et al 2005;Tarboush et al 2014;Masuda et al 2016). In this report we quantified the differences in mitochondrial number, size, complexity and 3-D distribution in zebrafish cone subtypes.…”
Section: Comparisons Of Cone Mitochondria Between Species and Cone Sumentioning
confidence: 94%
“…Like cones in other species (T. Ishikawa & Yamada 1969;Knabe & Kuhn 1996) zebrafish cones form megamitochondria, maintained by the enlargement factor ES1 (Masuda et al 2016;Utsumi et al 2020). While we did not detect daily changes to es1 mRNA transcripts in whole retinas, we observed a small population of juxtaposed megamitochondria in all cones throughout the day.…”
Section: Mitochondrial Size In Photoreceptorsmentioning
confidence: 95%
See 1 more Smart Citation
“…Implicated genes of particular note included DNAJC19 and those involved in oxidative stress (GSTM1) and mitochondrial biogenesis (GATD3A) (31,32).…”
Section: Rna-seq Identifies Changes In Gene Expression Related To Dcmmentioning
confidence: 99%